Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s11671-019-3208-3
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Cell-Targeting Drug Delivery System Based on Aptamer-Modified Mesoporous Silica Nanoparticles

Abstract: How to deliver chemotherapeutic drugs efficiently and selectively to tumor cells to improve therapeutic efficacy remains a difficult problem. We herein construct an efficient cell-targeting drug delivery system (Sgc8-MSN/Dox) based on aptamer-modified mesoporous silica nanoparticles that relies on the tumor-targeting ability of the aptamer Sgc8 to deliver doxorubicin (Dox) to leukemia cells in a targeted way, thereby improving therapeutic efficacy and reducing toxicity. In this work, Sgc8-MSN/Dox showed sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Incubation of aptamer-modified and bare NPs with MCF-7 cells (that overexpress MUC-1 protein) showed higher uptake levels of aptamer-functionalized NPs when compared to the bare NPs. Further examples of aptamers as ligand for active uptake are reported by Gui et al (2019) and Yang et al (2019b). Yang et al (2019b) modified the surface of mesoporous silica nanoparticles (MSNs) with Sgc8 aptamer able to bind protein tyrosine kinase-7 (PTK-7) on human acute T lymphocyte leukemia cells.…”
Section: Active Uptakementioning
confidence: 99%
“…Incubation of aptamer-modified and bare NPs with MCF-7 cells (that overexpress MUC-1 protein) showed higher uptake levels of aptamer-functionalized NPs when compared to the bare NPs. Further examples of aptamers as ligand for active uptake are reported by Gui et al (2019) and Yang et al (2019b). Yang et al (2019b) modified the surface of mesoporous silica nanoparticles (MSNs) with Sgc8 aptamer able to bind protein tyrosine kinase-7 (PTK-7) on human acute T lymphocyte leukemia cells.…”
Section: Active Uptakementioning
confidence: 99%
“…Besides, Sweeney et al have attached a bladder-cancer specific peptide named Cyc6 to MSN for active targeting [ 130 ]. Apart from small molecules, peptides and antibodies, the synthetic single-stranded DNA or RNA oligonucleotides (aptamers) have been used to decorate MSN for targeting cancer cells [ 131 , 132 ]. Moreover, Nguyen et al have shown the Toll-like receptor 9 mediated delivery of mesoporous silica cancer vaccine (antigen) to the dendritic cells (the body’s most professional antigen presenting cells) [ 133 ].…”
Section: Surface Modification Of Msn For Passive and Active Targetmentioning
confidence: 99%
“…This approach led to the intracellular accumulation of doxorubicin and restored the sensitivity of breast cancer cells to doxorubicin [56]. In a recent work, Yang and colleagues [57] used mesoporous silica NPs (MSNPs), which are internalized by endocytosis, to target a human acute lymphoblastic leukemia (ALL) cell line. MSNPs were loaded with doxorubicin, and their surface was decorated with aptamer Sgc8, which specifically recognizes the protein tyrosine kinase-7 (PTK-7) on the membrane of ALL cells [57].…”
Section: Use Of Nanoparticles For Redox-controlled Drug Deliverymentioning
confidence: 99%
“…In a recent work, Yang and colleagues [57] used mesoporous silica NPs (MSNPs), which are internalized by endocytosis, to target a human acute lymphoblastic leukemia (ALL) cell line. MSNPs were loaded with doxorubicin, and their surface was decorated with aptamer Sgc8, which specifically recognizes the protein tyrosine kinase-7 (PTK-7) on the membrane of ALL cells [57]. This system allows specific doxorubicin uptake by leukemia cells, and, as MSNPs release the drug slowly and preferentially under the acidic conditions, it results in sustained drug accumulation at tumor sites, thus enhancing the specific anticancer effect of doxorubicin.…”
Section: Use Of Nanoparticles For Redox-controlled Drug Deliverymentioning
confidence: 99%